ABDURRAHMAN WAHID: STUDY PEMIKIRAN TENTANG RELASI AGAMA DAN NEGARA - Pamungkas, Mahar Tri; Joebagio, Hermanu; Bachri, Saiful (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2016)
This research is aimed at to know: (1) genealogy biography of Abdurrahman Wahid; (2) intellectual abroad of Abdurrahman Wahid when he was teenager; and (3) Abdurrahman Wahid?s thought in the context of diversity of Indonesia and the relation of religion and state.The method that is used in this research is phenomenology qualitative method. The steps done in this research covers: collecting data, data reduction, data display, and drawing conclusion. The sources of the research are interview and document. The techniques of collecting data in this research are literature review and interview. The validity of the data is done by data source triangulation. The technique of analyzing data is interactive technique, by reducing and displaying data while collecting data. The data in the form of field note is the data that has been dig and noted. The field notes then become systematic and logic data display based on the problem statements. The collecting data process that has been done, then the researcher arranges the discussion and draws the conclusion. Based on the results of the research, it can be concluded that: (1) Abdurrahman Wahid is one of prominent figure of Indonesia has to be descendant of aristocrat of Hasyim Asy?ari who was founder of Tebuireng Muslim Boarding School and founder of Nahdlatul Ulama, so that Abdurrahman Wahid gets the important position in the society; (2) Abdurrahman Wahid has education and social intercourse experience that makes he has liberal, moderate, and progressive thought; (3) there is mutual symbiotic correlation between religion and state, both working together in the community, nation and religion protects religious life even guiding life in the country. Symbiotic relation of religion and state in Indonesia is stated in Pancasila, Indonesian Constitutional Law 1945, and Bhinneka Tunggal Ika slogan. Pancasila and the Constitution of 1945 is the final form of the best. Pancasila and the Constitution of 1945 into a platform capable of shelters a diversity of the Indonesian community. Abdurrahman Wahid?s thought about relation between religion and state based on fiqh perspective by adapting the condition of Indonesian social-cultural. The material about Abdurrahman Wahid can be inserted in History subject grade 12st Social in the material of the government system that have ever existed in Indonesia, starting from Old Order, New Order Government, until Reformation. The teacher should not only teach about the characteristics of government, how the running of the government is, the plus and minus of the government system, but also tell about the model of the figures that had ever been the leader in that government system. For example is Abdurrahman Wahid. We can take his positive behavior that shown up until now as a learning and good model. Those behaviors are democratic, anti-discrimination, and respect about pluralism.